Neurological manifestations in musculoskeletal disorders - Tsouni, Pinelopi; Kuntzer, Thierry; Ochsner, François (Revue médicale suisse, 2014)
Musculoskeletal disorders are a crossroad among diverse specialties: neurology, rehabilitation, orthopedics, occupational medicine and psycho-traumatology. They are integrated into occupational medicine and encompass overuse syndromes, repeated micro-trauma and focal compressive neuropathies linked with professional or sports' activity. Neurological manifestations are omnipresent. Yet, their importance is not always recognized despite frequent resort to neurologists specialized in peripheral nervous system disorders and neurophysiology, as well as, to behavioral cognition specialists. Therapeutic approaches require preventive and work organization measures, neurophysiologic investigations and imaging in expert hands, and conservative treatment with physiotherapy, with or without paraneural and intra-articular injections.